(3GdGbJUGO GdgfOSj (B/s - (3GdYHGOj, LeGd GUHjMGJs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2008)
(3eOGNd YGeI, MSGHGJ GdJcGaD, Jbjje GdHOGFd GdgfOSjI hebGQfJgG hGJNGP GdbQGQGJ HTCfgG, JWHjbGJ aj GdGbJUGO GdgfOSjs
(3HHdjhZQGajG(B: 291-292 (3cTGa eUWdMGJ(B: (3U(B.281(3; edGMb(B: (3U(B. 251s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdgfOSjs